Boundedness of Vector-Valued Intrinsic Square Functions in Morrey Type Spaces - Hua Wang (Journal of Function Spaces, 2014)
We will obtain the strong type and weak type estimates for vector-valued analogues of intrinsic square functions in the weighted Morrey spaces Lp,κ(w) when 1≤p<∞, 0<κ<1, and in the generalized Morrey spaces Lp,Φ for 1≤p<∞, where Φ is a growth function on (0,∞) satisfying the doubling condition.